Original Anticonvulsant Urea Derivative Alters the Properties of Benzodiazepine Receptors Central and Peripheral Types in the Cerebral Cortex of Heavy Drinkers Rats - Shushpanova T. V. Tamara Vladimirovna; Solonskii A. I. Anatoly Vladimirovich; Bokhan N. A. Nikolay Aleksandrovich; Novozheeva T. P. Tatjana Petrovna; Udut V. V. Vladimir Vasiljevich; Arbit G. A. Galina Aleksandrovna; Filimonov V. D. Viktor Dmitrievich (2016, 2016)
Title screen